Transfering Shrunken 2 (Sh2) gene coding for adp-glucose pyrophosphorylase enzyme into some inbred maize lines by Agrobacterium tumefaciens mediated gene transfer - Luong, Tran Thi; Thu, Nguyen Thi; Ninh, Nguyen Thuy; Thanh, Nguyen Duc (Academia Journal of Biology, 2014)
The Shrunken 2 (Sh2) gene was proved to be involved in starch biosynthesis as it codes for two large subunits of ADP-glucose pyrophosphorylase - an enzyme that plays an important role in regulating starch biosynthesis in cereal crops. The aim of this study was to transfer Sh2 gene into some inbred maize lines and regenerate transgenic maize plants possessing transgene for further study of the role of Sh2 gene in the enhancement of starch biosynthesis in maize. The Agrobacterium tumefaciens strains C58 and DHA105 harboring transformation vector pCambia1301/Ubi/Sh2 containing Sh2 gene and monocot-specific Ubiquitin promoter were used to transfer Sh2 gene into immature embryos of the maize lines. PCR amplification of Ubi and Sh2 genes was performed to confirm the presence of the transgene in T0 transgenic plants. While, Southern and Northern hybridizations were carried out to confirm stable integration and expression of Sh2 gene in T0 and T1 transgenic plants, respectively. Transgenic plants were regenerated from transformed calli of six maize lines H95, H240, H26, H14, H4 and CML161 with the transformation frequencies from 1.08 to 1.77%. A. tumefaciens strain DHA105 gave higher transformation frequencies than that of C58 strain and the values ranged from 1.60 to 4.31%. The transgenic maize plants possessed 1 to 3 copies of transgene. Many transgenic plants grew normally and set seeds. The study of the effect of transgene in starch biosynthesis in transgenic maize lines will be performed.